Suture obliteration patterns in wolves and a comparison to dogs - Megan Bieraugle; Abbey E. Wilson; Tatiana Nomokonova; Naima Jutha; H. Dean Cluff; Robert J. Losey (Scientific Reports, 2025)
Abstract Age-related patterns in cranial suture and synchondrosis obliteration in 371 known-age North American grey wolves (Canis lupus) are examined to assess their utility in estimating the age of archaeological and paleontological wolf crania. Differences in age-related obliteration patterns between these wolves and 576 known-age domestic dogs (Canis familiaris) also are explored. Domestication has likely altered the growth and development of dog crania in relation to that of wolves, but these processes remain poorly understood. Wolf total suture obliteration score and age were positively correlated, indicating that the level of suture obliteration can be used to track age to some extent. Wolf sex and dietary patterns had no meaningful effects on this correlation. Mesocephalic or dolichocephalic dogs generally begin exhibiting more extensive suture obliteration than wolves during early adulthood, at about 2–4 years of age. This pattern of more extensive obliteration persists throughout the lifespan, with dogs tending to experience more obliteration in the observed sutures and synchondroses. Several interrelated factors may contribute to this pattern, all outcomes of domestication, including differences in physical strains in the cranium, alteration of development and ageing, and the emergence of diverse head shapes that relate in part to suture closure timing.